AN ASSAY METHOD FOR LEUKOCYTE PYROGEN - Murphy, P. A. (The Rockefeller University Press, 1967)
A method for assaying leukocyte pyrogen is described which is shown to remain valid despite the presence of very large amounts of bacterial endotoxin. It uses a combination of two procedures to inactivate endotoxin: incubation in normal rabbit plasma for 24 hr at 37°C, and injection into rabbits rendered refractory to endotoxin. The validity of the assay was confirmed by formal statistical methods. A simplified assay method is also described which lacks full statistical validity, but is more suitable for routine use.